1104 Long-Term Outcome of Term Newborns with Perinatal Asphyxia - Predictive Factors. (October 2012) - Avasiloaiei, A; Dimitriu, C; Bivoleanu, A; Paduraru, L; Stamatin, M
Abstract : Perinatal asphyxia represents the second most important cause of death in the NICU and an important source of neurologic long-time sequelae. Aim: To identify long-term predictive factors for neurologic sequelae in term newborns with perinatal asphyxia. Material and Methods: We conducted a prospective study on 67 term newborns with perinatal asphyxia, admitted to our NICU between 2010–2011. The following parameters were followed: Apgar scores at 1, 5, 10 minutes, cord blood pH, neurologic disorders, creatine-kinase (CK), lactate dehydrogenase (LDH), total antioxidant status (TAS) at 4, 12, 24, 48, 72 hours and 7 days, follow-up after discharge until 18 months of age. Results: Incidence of perinatal asphyxia in the NICU was 3.76%. Mean Apgar score at 1 minute was 3.58 and at 5 minutes 5.33, thus indicating the efficiency of resuscitation. Mean blood cord pH was 7.04. During the first 12 hours of life, all newborns had neurologic disorders. After the first 72 hours, this aspect was only present in 53.7% of the newborns. TAS was lowest at 12 hours (0.92 mmol/L), not reaching normal values at any moment. Survival was 91.04% and was correlated with ph (p=0.012), CK (p=0.04), LDH (p=0.02), but not TAS (p=0.063). Neurologic sequelae decreased progressively, reaching 10.45% (n=7) at 18 months. CK and LDH were predictive for sequelae (p=0.01), but not the Apgar score or TAS (p=0.08). Conclusion: Routine determinations for blood cord pH, CK and LDH can become valuable markers of long-term outcome for newborns with perinatal asphyxia, while TAS remains for further research.